Neoadjuvant radiotherapy for myxoid liposarcomas: Oncologic outcomes and histopathologic correlations - Ahmet Salduz; Buğra Alpan; Natig Valiyev; Emre Özmen; Ayça İribaş; Fulya Ağaoğlu; Aysel Bayram; Bilge Bilgiç; Harzem Özger (Acta Orthopaedica et Traumatologica Turcica, 2017)
Objective: The aim of this study was to evaluate the histopathological features of primary extremity myxoid liposarcoma before and after neoadjuvant radiation therapy, and to evaluate the oncological outcomes of the patients. Methods: The study included 23 patients (16 men and 7 women with a mean age of 43 (24–69) years) with primary myxoid liposarcoma of the extremities, who were treated between January 1998 and December 2015. Inclusion criteria were histopathological confirmation of the diagnosis with both the initial biopsy and the resection specimen, and having undergone neoadjuvant radiotherapy. Demographic, clinical and histopathological data were evaluated. Results: Over a mean follow-up time of 55.2 (8–139) months, 5 patients (21.7%) died secondary to disease progression, leaving 18 patients (78.3%) still alive at the time of last follow-up. Only one patient (4%) experienced local recurrence and six (26%) patients developed distant metastases. Disease-free survival at 5 and 10 years were 66%; whereas, overall patient survival at 5 and 10 years were 78.1% and 71.0%, respectively. Tumor size (>15 cm) and presence of metastasis were significantly associated with increased overall mortality. On histopathology, necrosis was present in 12/23 resection specimens. Hyalinization/fibrosis and residual viable tumor was present in all specimens. Adipocytic maturation/cytodifferentiation was seen in 8/23 patients. Conclusion: Neoadjuvant radiotherapy was effective for myxoid liposarcomas histopathologically, although these histopathological features did not affect the patients' oncological outcomes. Favorable oncological outcomes were obtained with neoadjuvant radiotherapy, surgical resection and chemotherapy. Level of evidence: Level IV, therapeutic study. Keywords: Neoadjuvant radiotherapy, Myxoid liposarcoma, Histopathology, Outcomes